2022
DOI: 10.3389/fnut.2022.865257
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactams and Lactones With Antioxidant Potentials From Atractylodes macrocephala Discovered by Molecular Networking Strategy

Abstract: Atractylodes macrocephala rhizome (called Bái-zhú in China) has a long history as a functional food and herbal medicine in East Asia, especially China. Sesquiterpenoids are one of the main active compounds of Atractylodes macrocephala rhizome. This study aimed to explore the unknown sesquiterpenoids of A. macrocephala rhizome using a molecular networking strategy. Two new nitrogen-containing sesquiterpenoids, atractylenolactam A (1) and atractylenolactam B (2), and 2 new sesquiterpene lactones, 8-methoxy-atrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…AMP is widely used for its antioxidant, anti-inflammatory, anti-tumor, immunopotentiator, and intestinal health maintenance benefits [ 8 , 9 , 11 , 12 , 13 , 14 , 15 ]. In the present study, 400 mg/kg AMP significantly promoted WGR, SGR, and FE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMP is widely used for its antioxidant, anti-inflammatory, anti-tumor, immunopotentiator, and intestinal health maintenance benefits [ 8 , 9 , 11 , 12 , 13 , 14 , 15 ]. In the present study, 400 mg/kg AMP significantly promoted WGR, SGR, and FE.…”
Section: Discussionmentioning
confidence: 99%
“…AMP can reduce inflammatory damage and oxidative stress via the NF-κB signaling pathway [ 11 , 12 ]. AMP can also enhance antioxidant defense capacity by promoting the expression of glutathione peroxidase (GPx) and SOD [ 13 , 14 ], which are related to the Nrf2 signaling pathway [ 15 ]. However, few studies report the effects of AMP on aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, sesquiterpene lactams and lactones are the main active components of Atractylodes macrocephala , which perform excellent anti-inflammatory and antioxidant activities ( Bailly, 2021b ). Atractylodes are commonly used to heal gastrointestinal disorders due to their potential role in regulating intestinal microbiota ( Feng et al, 2020 ; Wang et al, 2022 ). Previous studies have indicated that several herbal medicines are usually combined to achieve the synergetic effect better than single herb based on their similar therapeutic properties ( Xu et al, 2022 ; Zhou et al, 2016 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, immunoregulatory polysaccharides are considered important macromolecules for stimulation of immune response, then gradually become a major research hot spot (1,2). Atractylodes macrocephala Koidz (A. macrocephala) has been used both as traditional medicine and functional food for hundreds of years in Asia, and it was approved as a functional food by the National Health Commission of the People's Republic Health of China (3)(4)(5). Polysaccharide from A. macrocephala (AMP) has a variety of biological activities, such as enhancing the ability of immunity, modulating effect on gastrointestinal motility and decreasing the blood glucose level (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%